Efficient Low-Temperature catalytic depolymerization of LLDPE into valuable compounds using H-ZSM-5 catalysts and water - Mei Ren; Jun Li; Manhong Huang; Donghui Chen; Xuelian Chen; Qi An; Songmei Sun (Fuel, 2024)

Design and Optimization of the Wall Climbing Robot for Magnetic Particle Detection of Ship Welds - Xuan Zhang; Minglu Zhang; Shilong Jiao; Lingyu Sun; Manhong Li (Journal of Marine Science and Engineering, 2024)
At present, numerous wall-climbing robots have been developed, and applied in ship manufacturing for weld detection to ensure safe navigation. Limited by rigid mechanical structure and complex detection, mostly existing robots are hardly to complete weld detection by using fluorescent magnetic particles. Based on permanent magnet adsorption, a wheeled wall-climbing robot is developed to realize the stable adsorption and flexible movement on ship wall. A detection mechanism is designed using a series and parallel flexible adaptation structure to keep cross yokes and detection area close for effective detection. A unified mechanical model is established by analyzing the angle between robot attitude and gravity, to solve safe adsorption and flexible movement for different detection conditions. Integrated the multisensor information and collaboration between control component, an automatic detection control workflow conforms to the standard process is proposed. Experiments show that the robot can move on curvature wall flexibly and stably, complete the weld detection with the standard process, and clearly display the shape and depth of the small defects (groove depth ≥ 30 μm) in standard specimen.

Underlying the mechanisms of pathogen inactivation and regrowth in wastewater using peracetic acid-based disinfection processes: A critical review - Yuqian Lin; Yunpeng He; Qiya Sun; Qian Ping; Manhong Huang; Lin Wang; Yongmei Li (Journal of Hazardous Materials, 2024)

Sucrose Metabolism Enzymes Affect Sucrose Content Rather than Root Weight in Sugar Beet (Beta vulgaris) at Different Growth Stages - Ke Shao; Zhenqing Bai; Manhong Li; Chao Yu; Jinwang Shao; Yaqing Sun; Guolong Li; Shaoying Zhang; Ruigang Wang (Sugar Tech, 2020)

Carbon Requirements of Some Nematophagous, Entomopathogenic and Mycoparasitic Hyphomycetes as Fungal Biocontrol Agents - ManHong Sun; XingZhong Liu (Mycopathologia, 2006)